Sugarcane Its Products and Sustainability - Kumar Ghimire, Bimal (IntechOpen, 2023)
This book discusses the most recent research on sugarcane production and its applications. It provides a comprehensive overview of the current technology of producing bioethanol from sugarcane to meet the global demands for biofuel. It also explores innovative technology to convert sugarcane into new value-added products. The book is designed to provide practical insights into the current challenges in the production of value-added products from sugarcane byproducts and their contribution to the sustainability of the sugarcane industry. It offers a broad understanding of major challenges related to the improvement of risk management strategies, as well as public policies to the energy market. It also presents precise and meticulous insight into the importance of abiotic stress affecting sugarcane productivity and morphological traits.